2013 IEEE International Conference on Systems, Man, and Cybernetics 2013
DOI: 10.1109/smc.2013.609
|View full text |Cite
|
Sign up to set email alerts
|

Fallen Person Detection for Mobile Robots Using 3D Depth Data

Abstract: Falling down and not managing to get up again is one of the main concerns of elderly people living alone in their home. Robotic assistance for the elderly promises to have a great potential of detecting these critical situations and calling for help. This paper presents a feature-based method to detect fallen people on the ground by a mobile robot equipped with a Kinect sensor. Point clouds are segmented, layered and classified to detect fallen people, even under occlusions by parts of their body or furniture.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 25 publications
(28 reference statements)
0
16
0
Order By: Relevance
“…In [22], the authors propose a pipeline working on just single RGB images extending a deformable part-based model to the multi-view case for viewpoint invariant lying posture detection. Like us, [23] proposes a pipeline working on single depth images. Putative candidates are found by means of a segmentation phase based on an Euclidean clustering.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…In [22], the authors propose a pipeline working on just single RGB images extending a deformable part-based model to the multi-view case for viewpoint invariant lying posture detection. Like us, [23] proposes a pipeline working on single depth images. Putative candidates are found by means of a segmentation phase based on an Euclidean clustering.…”
Section: Related Workmentioning
confidence: 99%
“…On the contrary, this work specifically addresses this problem by concatenating two classifiers. Unfortunately, neither the code or dataset of [23] are available making a direct comparison impossible. Finally, in [24], a method for detecting and locating the head of a person lying on the floor by means of a RGB-D sensor is proposed.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that using multiple Kinect sensors may be necessary to make further improvements in these areas (Stone & Skubic, 2015), but interference between the multiple near-IR light sources may present a challenge for this approach. One research team has mounted the Kinect on a robot that patrols its environment searching for fallen people (Volkhardt, Schneemann, & Gross, 2013), but this approach may not be tolerated well by older adults, particularly those experiencing dementia, paranoia, or delusions.…”
Section: Introductionmentioning
confidence: 99%
“…Detection of events has gained lots of attention in video surveillance domain, it is the case of research related to the identification of lying pose recognition [15,13], detection of people running [4,19], crowd safety [7,16], etc. In videos that include civil interactions, modeling the social behaviors of people plays an important role in describing the individual and group behaviors on crowded scenes [18].…”
Section: Introductionmentioning
confidence: 99%